Quantitation of IL-2Rp75 (CD122) expression on mononuclear cells in rheumatic disease. Issue 11 (November 1996) - Creamer, P; Hall, N D
Abstract : OBJECTIVE: To compare expression of the p75 chain of the interleukin-2 receptor (IL-2Rp75, CD122) on peripheral and synovial mononuclear cells in rheumatoid and non-rheumatoid inflammatory arthritis. METHODS: Peripheral blood (PBMC) and synovial (SFMC) mononuclear cells were isolated from subjects with rheumatoid arthritis (n = 16) and non-rheumatoid inflammatory arthritis (n = 12). PBMC were isolated from six healthy controls. Expression of CD122 was examined using indirect immunofluorescence and quantitative flow cytometry. RESULTS: There was no difference in IL-2Rp75 expression on PBMC from rheumatoid arthritis patients, non-rheumatoid arthritis patients, and controls. In subjects with rheumatoid arthritis there was no difference in IL-2Rp75 expression on PBMC and SFMC. However, in the non-rheumatoid arthritis group there was an increase in IL-2Rp75 expression on SFMC compared with PBMC (P = 0.0032). On SFMC there was a greater expression of IL-2Rp75 in non-rheumatoid arthritis than in rheumatoid arthritis (P = 0.0007). Expression was greater on CD8 positive cells and in subjects with shorter duration of disease. CONCLUSIONS: The p75 chain of the IL-2 receptor, an important T cell activation antigen, is not upregulated in synovial fluid. This appears to be a disease specific defect and provides further support for the concept of "frustrated" or incomplete T cell activation in this disease.